Peran Kepala Sekolah Dalam Peningkatan Manajemen Mutu Lembaga PAUD - Dwi Indah Anggraini (JURNAL BUNGA RAMPAI USIA EMAS, 2025)
The role of the principal includes not only administrative responsibilities, but also intelligent leadership that can influence and direct all components of the PAUD institution to achieve the desired educational standards. This article uses library research, which collects information by studying theories in various references that are closely related to this research. Literature study is used in the research method in this article. To improve the quality of the institution, the principal must have sufficient ability both in terms of academic and non-academic achievements. Improving the quality of educational institutions depends on the quality of the performance of the responsibilities held by the school principal. The job of an educational leader is to ensure that education runs smoothly. Principals as managerial institutions have duties and functions to ensure the implementation of education that has good quality for the institutions under their auspices.